Apical Rooted Cuttings Revolutionize Seed Potato Production by Smallholder Farmers in the Tropics - VanderZaag, P.; Pham, T.X.; Demonteverde, V.E.; Kiswa, C.; Parker, M.; Nyawade, S.; Wauters, P.; Barekye, A. (IntechOpen, 2021)
Potato apical rooted cuttings (ARC) originating from juvenile simple rounded leaf mother plants are a significant new way of transplanting and field growing of seed potatoes under smallholder field conditions in the tropical highlands. The aim of this paper is to highlight the development of the technology by researchers and farmers in Vietnam, Philippines, Kenya and Uganda. The development of cultivars with late blight resistance for which no source of tuber seed was available stimulated the creation of using ARC. The demystification of tissue culture by the 1980s greatly aided this development. The key hurdle was to multiply tissue culture plants in beds of growing media and maintain the physiological young stage of the mother plants from which apical cuttings could be repeatedly taken for several months to produce ARC for sale to farmers who demanded the new cultivars (cvs) with all the desirable attributes. The technology was first developed in warmer climates at lower elevations of less than 1,500 meters above mean sea level (mamsl) but gradually it was successfully developed at cooler climates in East Africa. The technology is well established in the highlands of Vietnam and Philippines. The largest family operation is producing over 4 million ARC annually. These high-quality ARC along with improved cvs have markedly improved yields of smallholder farmers, improving food security and increasing their income levels. In Kenya and Uganda there is a rapid adoption of ARC by seed producers, smallholder farmers and youths. The ARC revolution is bringing a great deal of excitement and promise of prosperity to remote poor highland communities.